USING TIO2 NANOFLUID FOR ENHANCING PERFORMANCE OF A WATER CHILLER - Saleh Mahdi, Qasim; Abd Al-Fattah Abood, Sahar; Jaber Nabhani, Baydaa (Journal of Engineering and Sustainable Development, 2015)
In the present work, an experimental study is carried out to enhance the performance of the water chiller system by using nanofluid (water+TiO2 ) on the shell side of the chiller with different volume concentrations (0.05%, 0.075%, and 0.1%). Experimental work includes two parts; In the first one COP of the system is calculated by using two alternative refrigerants (R-407c and R-134a). In the second part, the optimum COP is found using various concentrations of TiO2 nanofluid for systems with an alternative refrigerant. Experimental results show that the COP of R-134a is better than R407c which will be used in the second part of the present study with nanofluid on the shell side of the system. The COP with (0.1%) nanofluid has been found to increase by (8.5%).